Design of Mechanical Systems for a Residential Building in Hebron - Mar’ee, Ahmad; Abu Sarhan, Mohammad (جامعة بوليتكنك فلسطين , و كلية الهندسة , ميكانيك, 2017)
This project aims to design mechanical systems for a building in Hebron that consists of 8 floors, two basements floors one for cars parking and the another is apartment , The others sex floors is apartments, and total area about 2136 m2, the design includes water networks, drainage system also the project concerns design of Firefighting system , and heating ventilationair conditiong (HVAC) by (VRF systems).
Design of Mechanical Systems for a Residential Building in Hebron
cd, 30161, in the store , ميكانيك 8/2017, no of pages 123
Keywords: Thermal Comfort,ASHRAE,Convection heat,Heating load,Cooling load,Water supply,Drainage,Pipe size,Gas,Pump,VRF